Development of A Recovery Model For Hockey Athletes Based on Propioceptive Neuromuscular Facilitation (PNF) - Wibowo, Tri; Hardiyono, Bayu; Melianty, Selvi; Sukmawati, Noviria (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
The research was conducted because of the need for a recovery model that can be used by hockey athletes. Research and development was conducted to produce a product in the form of a Recovery model for Hockey athletes based on Propioceptive Neuromuschular Facilitation (PNF). The research was conducted using the research and development method of the Borg and Gall model. Research data were collected using a validation questionnaire, an attractiveness questionnaire, and documentation. Data analysis of research results using Content Validity Index and Content Validity Ratio techniques. The results of the study are recovery model products for hockey athletes based on Propioceptive Neuromuschular Facilitation (PNF) developed according to ten steps from the Borg and Gall model, namely research and information collection, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, and dissemination and implementation. The recovery model product for hockey athletes based on Propioceptive Neuromuschular Facilitation (PNF) shows the average value generated is 0.64 with the interpretation of high validity so that it is feasible and effective to use in the recovery activities of Hockey athletes. The recovery model product for hockey athletes based on Propioceptive Neuromuschular Facilitation (PNF) developed is very attractive to users with a percentage of attractiveness of 87.33% so it is possible that users will use the developed product in recovery activities.